Essentiality of stakeholder management for university survival - Khanyile, M. (South African Journal of Higher Education, 2020)
Universities are struggling to identify and analyse who their stakeholders are, what stake(s) they claim; what threats or opportunities stakeholders present; what responsibility they have towards stakeholders; and to conflate the terms ‘publics’ and ‘stakeholders’. Management of stakeholders entails a symbiotic and epistemological relationship between system-in-focus, stakeholders and the environment. The reductionist approach cannot assist in gaining an understanding of what stakes stakeholders claim. A university is expected to identify its stakeholders and their needs before defining priorities and relational strategies for each stakeholder. As a complex adaptive system operating in complex, ever-changing, diverse and shifting environments, a university needs strong stakeholder management strategies to continually adapt to the needs and expectations of both the university and its stakeholders. Stakeholder salience and identification could enable universities to understand the typology of stakeholder attributes, as well as assist in defining taxonomies relevant to each scenario. In order to enable universities to respond to stakeholders’ competing needs, a ‘strong management’ is suggested in the educational realm, with a fundamental paradigm shift to the notion of ’economic rationalism’ in the provision of educational services. This conceptual article seeks to underscore the importance of managing stakeholders for the long-term survival of the university.